Waiting room group treatment of sickle-cell disease outpatients - Santos, Ana Rita Ribeiro dos; Miyazaki, Maria Cristina de Oliveira (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Waiting room group treatment of sickle-cell disease outpatients. Studies on sickle-cell disease suggest that the emotional problems associated with the condition are related to the symptoms experimented by the patients. Both treatment and symptoms make school adjustment hard for the children, and frequently lead to parent overprotection. They way patients cope with the disease is important to reduce hospitalizations and visits to the physician patients and caretakers can receive a lot of information from the interdisciplinary team with the use of group activities and workbooks. The information may lead to behaviors that are helpful to improve adherence and the development of coping strategies.